Application of T-S fuzzy controllers on an HVAC system - Teng, Long (2020)
This paper focuses on designing fuzzy controllers for a kind of Heating, Ventilation, and Air Conditioning (HVAC) systems. A kind of fuzzy method based on T-S fuzzy models with nonlinear local feedbacks is applied to a specific HVAC system. Firstly, an augmented HVAC system model is got based on an existing model. Then control with T-S fuzzy systems with nonlinear local models is reviewed. The control gain is got by solving a set of linear matrix inequalities (LMIs) where H ∞ performance is considered. Finally, simulations and comparisons are executed to illustrate the effectiveness of this kind of fuzzy methods.